Periodic Flow of Non-Newtonian Fluid Over a Uniformly Heated Block With Thermal Plates: A Hybrid Mesh-Based Study - Hussain Majeed, Afraz; Mahmood, Rashid; Hamadneh, Nawaf N.; Siddique, Imran; Khan, Ilyas; Alshammari, Nawa (Frontiers in Physics, 2022)
In this work, we analyze the characteristics of periodic flows in non-isothermal viscous fluid over a heated block in the presence of thermal plates at Reynolds number . The unsteady, incompressible Navier Stokes (NS) equations with suitable initial and boundary data in 2D are executed by finite element technique using a highly refined hybrid mesh. The temporal discretization is performed by an implicit stable backward differencing in time and a stable choice of finite elements from the finite element library for spatial discretization. The discrete non-linear system arising from this discretization is linearized by Newton’s method and then solved through a direct linear solver PARDISO. For this forced convective study, the range of dimensionless parameters i.e., Prandtl number is varied in 1 to 10, the power-law index is from 0.6 to 1.4 with a low Grashof number varying as to produce forced convection regime, respectively. For the authentication, we have compared our results with literature at a similar configuration. After simulation, the results are accomplished in velocity profile, pressure, isotherm contours, drag and lift coefficients (trajectories motion), and average Nusselt number (〖Nu〗_avg ), etc. are considered. For convergence of solution at low shear rate Cross-Wind Stabilization (CWS) function has been incorporated. It is observed that 〖Nu〗_avg become oscillatory for shear-thinning case (n<1) while for shear-thickening cases (n>1) it converges to a single value. Furthermore, the drag (C_D ) and lift (C_L ) coefficients are more pronounced for shear-thinning cases (n<1) as compared with shear-thickening cases (n>1).